Psychological aspects of the polycystic ovary syndrome. (February 2014) - Farkas, Judit; Rigó, Adrien; Demetrovics, Zsolt
Abstract An overwhelming majority of scientific literature on the polycystic ovary syndrome has utilized a medical approach to analyse the disorder and only few studies have investigated its predisposing psychological factors. This literature review sheds light on the fact that this gynaecological disorder of endocrine origin, which is becoming more frequent, can be associated with a great number of psychological symptoms (e.g. depression, anxiety, body image dissatisfaction, eating and sexual disorders, and low life satisfaction). Thus, the syndrome is significant from a therapeutic point of view as well. Authors review the psychological correlates of specific symptoms, their relationships with other psychological syndromes and analyse the psychosocial background of the disorder as well as the possibilities of psychotherapy.